Analyse multi-niveaux de l’économie de la RSE : le cas des entreprises du secteur banane au Cameroun - Thomas Borrell (Revue de la Régulation)
This research, based on a case study, aims at assessing systemic effects of corporate social responsibility (CSR) instruments operated by the firm’s management. Hence, in addition to the “double-effect” principle, the research must take into account that CSR operations impact people beyond the initial target, and besides the whole social structure. Accordingly we have deviced an assessment methodology, grounded on the IAD-SES (“socio-ecological systems”) heuristic framework which we have developed and applied to the study of CSR in the cameroonian banana sector. This results in demonstrating that, along with the positive impacts we have assessed, this CSR managerial operations contribute to, or even strengthen, the structural causes of the social problems they were supposed to solve.